Effectiveness Of Using Liquid Organic Fertilizer From Oil Palm Empty Fruit Bunch Fiber Waste On Plants Growth - Auni Hasyilah, Abu Yazid (2022)
Liquid organic fertilizer has been created to reduce farmed plants' reliance on inorganic fertilizers. It is based on oil palm fruit bunch fibre (OPEFBF), a by-product of palm oil mill processing used as an organic fertilizer. This study aims to find the optimal formulation of liquid organic fertilizer from oil palm empty fruit bunch fibre waste and assess its efficacy on plant development and soil parameters. The first step included drying the fibre and converting it to liquid organic fertilizer. Three formulations of liquid organic fertilizers with different substrate amounts were created (oil palm fibre fruit bunch fibre, molasses, urea, and bio-activator). The second step included fertilizing the Sissoo Spinach (Alternanthera Sissoo) and Rubber Plant (Ficus Elastica) using liquid organic fertilizer. The experiment was using a Complete Randomized Design and consisted of five treatments: Formulation A (OPEFBF waste 1 kg + Bio-activator 0.04 L + Molasses 50 g + Cattle Urine 2 g), Formulation B (OPEFBF waste 1 kg + Bio-activator 0.04 L + Molasses 50 g), Formulation C (OPEFBF waste 1 kg + Molasses 50 g), commercial fertilizer (readymade fertilizer), and control (plant without adding fertilizer). Once a week, the liquid organic fertilizer was sprayed on the plants. Data on growth such as the number of leaves, plant height, length, and width of leaf were collected. The plant growth results indicated that Formulation A provided the greatest growth performance, which was comparable to that of plants fed with commercial fertilizer. This investigation established that Formulation A has growth-promoting effects comparable to commercial fertilizer. Additionally, it demonstrates that this product is organic and serves as a rich supply of nutrients for the plant.